The Development Of E-learning System Application Based On Cloud - M Budi Hartanto (Prosiding International conference on Information Technology and Business (ICITB), 2017)
NOSQL databases are in the base of storage of Big Data. They can store large volumes of structured, semi-structured, and unstructured data. Using NOSQL database to store ontology can take advantage of Big Data storage. This give benefits in storing Indonesian folk songs storage that usually vary and have sparse / incomplete data. This paper illustrates an approach to store data of Indonesia folk songs in NOSQL based database. We choose to deal with MongoDB. We present our steps of approach in storing, collecting, analyzing and retrieving ontology on NOSQL based database. Keywords : Ccloud Computing, E-learning Systems, Implementation, and Strategies.